2024
DOI: 10.1109/tem.2021.3088518
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Industry 4.0 Technologies in Mitigating Supply Chain Disruption: Empirical Evidence From the Australian Food Processing Industry

Abstract: Supply chain disruption refers to a breakdown, often caused by an unforeseen incident or risk, in a supply chain's production or distribution process. Contemporary supply chains are globalized, complex, and extended, exhibiting an increased vulnerability to a multitude of risks and disruptions. However, the current trend of real-time data exchange through smart technologies, also known as industry 4.0, provides significant opportunities to reshape the conventional business operations and effectively cope with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 67 publications
2
48
0
1
Order By: Relevance
“…Collaboration: Enterprise Quality Management System (EQMS) technologies can allow businesses to optimize and synthesize quality systems to improve compliance and efficiency. Quality 4.0 is designed to leverage modern technology and techniques, such as social listening and blocking, to analyze factors such as customer satisfaction and a more profound sense of component and product distribution across supply chains [ 105 , 106 ].…”
Section: Methodologiesmentioning
confidence: 99%
“…Collaboration: Enterprise Quality Management System (EQMS) technologies can allow businesses to optimize and synthesize quality systems to improve compliance and efficiency. Quality 4.0 is designed to leverage modern technology and techniques, such as social listening and blocking, to analyze factors such as customer satisfaction and a more profound sense of component and product distribution across supply chains [ 105 , 106 ].…”
Section: Methodologiesmentioning
confidence: 99%
“…Several studies have identified tactical and operational challenges in the digitalisation of traditional value chains, such as the lack of a skilled workforce and the limited availability of financial resources [18]- [20]. Despite the few empirical studies on the barriers of digitalisation, a more integrated view is required so that companies can reflect upon individual operations and system-level challenges to envision the necessary digital interventions [21], [22]. Therefore, a major gap towards the digitalisation of business processes can be attributed to the lack of understanding about how manufacturing firms can develop digital strategies for integrating and deploying digital technologies in operations [23], [24].…”
Section: Introductionmentioning
confidence: 99%
“…This gap is further amplified by the fact that companies have established business strategies such as lean, agile and leagile [18], [19], [21], which are characterised by dominant structural elements that render digital transformation even more challenging. In this regard, the greatest peril in the digitalisation of existing manufacturing operations refers to the lack of strategies that could inform and catalyse such transformation [22], [23], [25], [26].…”
Section: Introductionmentioning
confidence: 99%
“…The fourth revolution has started recently and emerged as a result of the convergence of physical, biological, and digital domains [5]. The fourth industrial revolution (called Industry 4.0 or 4IR) has been successful in increasing the food production quantity as well as quality [6,7]. For example, smart sensors, as an element of 4IR, can be used to sort products according to their physical, chemical, and other properties (this will be more explained later in this paper).…”
Section: Introductionmentioning
confidence: 99%